Influence of Anion and pH on the Electrochemical Co-Deposition and Transformation of Iron Oxy-Hydroxide (2013)
Goethite (α-FeOOH) and lepidocrocite (ᵧ-FeOOH) are two common iron and steel corrosion products. The study of goethite and lepidocrocite is an interesting way to better understand the corrosion processes of iron and its behaviour in different environments. In this work the co-deposition of iron oxides and their transformation on inert subtracts were studied at room temperature. The films were obtained by electro-deposition using solutions containing Cl-, SO42- and Fe2+at different pH on platinum disks. Linear polarisation, amperommetry, electrochemical impedance and spectroscopy techniques were used in this study. Anodic polarisation curves showed a current shoulder at low anodic polarisation and a current peak at higher polarisation. The shoulder observed at low anodic polarisation corresponded to the formation of a precursor compound like Fe2+-Fe3+ hydrated oxide, which is later transformed to an oxy-hydroxide compounds. The electrodeposition of goethite and lepidocrocite occurs, firstly through formation of a green rust film, characterised by a shoulder in the polarisation curves, and subsequently through formation of an iron oxy-hydroxide film. The anion and the pH of the electrolyte played an important role in the formation and further transformation of the iron oxides compounds on the film. It was corroborated that the Cl- ions and high pH stimulated the green rust and final oxyhydroxide film formation, while the SO42- ions and low pH retarded the formation of these compounds.